EFEKTIVITAS METODE PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN KETERAMPILAN BEKERJASAMA SISWA MATA PELAJARAN SKI - Lantansya, Dhea Siskha; Rofi'ah, Siti (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2023)
This study used a quantitative approach with a Pre-Experimental Design with the One-Group Pretest-Posttest Design type. Collecting data from this study using observation techniques, interviews, questionnaires and documentation. The number of samples taken 30% of the population. The collected data were analyzed using the data normality test, data homogeneity test and hypothesis testing which was completed with the help of the SPSS 17.0 computer program for windows. Based on the research it was found that: 1. Process The Snowball throwing method is an appropriate teaching and learning strategy in Madrasah Ibtidaiyah. Because learning will be effective if the learning process is carried out in a pleasant atmosphere so that children become enthusiastic about learning. 2. Using the Snowball Throwing method in Islamic Cultural History subjects can be used to form cooperative skills in increasing interaction between students. 3. The Snowball Throwing method is very effective for improving students' cooperation skills, as seen in table 4. That is, the significant value is less than 0.05, namely Sig. (0.011) < 0.05 so H0 is rejected, Ha is accepted. This shows that the average result of the questionnaire after treatment is higher compared to the average result of the questionnaire before treatment. It can be said that there is an influence on the effectiveness of the Snowball Throwing learning method in improving students' collaboration skills in SKI subjects at MI Sulaimaniyah Kauman. Keywords: Effectiveness, Snowball Throwing, Teamwork Skills